ПРОБЛЕМА ФОРМУВАННЯ КУЛЬТУРИ ПЕДАГОГІЧНОГО СПІЛКУВАННЯ В КОНТЕКСТІ ДІАЛОГІЧНИХ НАВЧАЛЬНИХ СИТУАЦІЙ (Педагогіка вищої та середньої школи, 2006)
This article reveals some questions design with the formation o f the culture of pedagogical communication of the future teachers, proves the necessity of building of dialogue training situations.